Pengaruh Kemajuan Teknologi Komunikasi Terhadap Perkembangan Sosial Anak - Putri Nur Anggraeni; Syafa Herdiani; Tin Rustini; Muh. Husen Arifin (FKIP, Universitas Palangka Raya, 2022)
The increasing use of technology today makes the world of technology more sophisticated. The development of technology today is inseparable from the development of communication technology, communication that used to take a long time to be delivered, now with technology everything becomes very fast and as if there is no distance. The existence of rapidly developing technology can make changes in patterns of social interaction in people's lives. Advances in technology that were originally created to provide convenience for human activities can lead to new alienation, such as the waning of a sense of solidarity, togetherness and friendship. This is caused by misuse of technology and communication, excessive use of technology without thinking about its impact, such as the vulnerability of estrangement between humans or lack of direct communication due to excessive use, one of which can also affect social development in children